At the nexus of vulnerability: Multilingualism in development - Hyltenstam, Kenneth; Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
This document was written in the early years of this century, about 15 years ago. It emerged out of more than a decade's engagement in matters of multilingualism, language, politics and education in Mozambique specifically, and Southern Africa more generally, that we had been involved in through the Centre for Research on Bilingualism at Stockholm University. The document itself was written at the request of SIDA, the Swedish International Development Cooperation Agency, and its research wing, SAREC, that had funded the majority of projects in language and education up until that point. The idea was to craft the outlines in a working document of a more comprehensive and sustained policy, or action plan, on issues of language in developing contexts. This was at a time of a growing awareness in the organization that its key funding areas - democracy, poverty, education, youth - involved language in much more complex ways than hitherto envisaged, and that a specialist document written for the layman might enlighten and provide direction.